Evaluation of the Liver Disease Information in Baidu Encyclopedia and Wikipedia: Longitudinal Study - Sun, Fei; Yang, Fuchun; Zheng, Shusen (JMIR Publications, 2021)
BackgroundThe internet has changed the way of people acquiring health information. Previous studies have shown that Wikipedia is a reasonably reliable medical resource, and it has been ranked higher than other general websites in various search engines. Baidu Encyclopedia is one of the most popular encyclopedia websites in China. However, no studies have shown the quality of the content provided in the Baidu Encyclopedia. ObjectiveThis study aimed to evaluate the quality of liver disease information provided by Wikipedia (in English) and Baidu Encyclopedia (in Chinese) and to perform a comparison of the quality and timeliness of the articles published in these two encyclopedias. Moreover, a 3-year follow-up study was conducted to compare if the information in both these websites was updated regularly over this period. MethodsWe searched for information on liver diseases by using the International Statistical Classification of Diseases and Related Health Problems 10th Revision Version 2016 codes on Wikipedia (in English) and Baidu Encyclopedia (in Chinese). The quality of the articles was assessed using the DISCERN instrument, which consists of 3 sections. We recorded the latest editing date of the webpages and calculated the date interval to evaluate the update timeliness of these websites. ResultsWe found 22 entries on liver diseases in Baidu Encyclopedia and 15 articles in Wikipedia between September 15, 2016, and September 30, 2016, and we found 25 entries in Baidu Encyclopedia and 16 articles in Wikipedia between September 15, 2019, and September 30, 2019. In section 1 of the DISCERN instrument, the mean (SE) scores of Baidu Encyclopedia entries were significantly lower than those of Wikipedia articles. In section 2 and section 3 of the DISCERN instrument, the DISCERN scores of Baidu Encyclopedia entries were lower than those of Wikipedia articles, but the differences were not statistically significant. The total DISCERN scores of Baidu Encyclopedia entries were significantly lower than those of Wikipedia articles. The update interval of the entries in Baidu Encyclopedia was found to be significantly longer than that of the articles in Wikipedia. ConclusionsThis study shows that the quality of articles and the reliability of the research content on liver diseases in Wikipedia are better than those of the entries in Baidu Encyclopedia. However, the quality of the treatment choices provided in both Wikipedia and Baidu Encyclopedia is not satisfactory. Wikipedia is updated more frequently than Baidu Encyclopedia, thereby ensuring that the information presented has the most recent research findings. The findings of our study suggest that in order to find accurate health information, it is important to seek the help of medical professionals instead of looking for a prescription amid the confusing information provided on the internet.